Micro- and nanoplastics in granular sludge systems: mechanisms of disruption, retention, and microbial adaptation in wastewater treatment technologies - Alfonz Kedves; Orsolya Kedves; Edit Mikó; Zoltán Kónya (Water Research X, 2025)
Microplastics (MPs) and nanoplastics (NPs) are increasingly recognized as disruptive agents in biological wastewater treatment systems. Granular sludge-based technologies, including aerobic granular sludge (AGS), anaerobic granular sludge (AnGS), anammox granular sludge (AxGS), and microalgal-bacterial granular sludge (MBGS), are particularly susceptible to interference by these pollutants. This review synthesizes current mechanistic insights into how MPs and NPs influence sludge stability, focusing on their effects on extracellular polymeric substances (EPS), oxidative stress responses, and microbial community structure. Our analysis identifies marked system-specific vulnerabilities, with AxGS and AnGS showing heightened sensitivity to EPS loss and reactive oxygen species accumulation, whereas MBGS exhibits comparatively greater resilience. Notably, nanoplastics tend to exert more severe effects than microplastics due to their higher reactivity and deeper biofilm penetration. Among the polymers studied, polystyrene, polyethylene terephthalate, and polyvinyl chloride display the most pronounced toxicity, impairing nutrient removal and microbial cohesion. In contrast, low concentrations of biodegradable plastics such as polylactic acid may stimulate EPS production and support microbial adaptation. A key contribution of this review is the comparative evaluation of granular systems within a unified framework, highlighting both shared and divergent plastic response mechanisms. In doing so, we expose critical knowledge gaps related to aged plastic behavior, combined pollutant effects, and microbial functional gene responses. We argue that addressing these gaps requires long-term, environmentally realistic studies using integrative methods such as metagenomics and metabolomics. This work provides a consolidated perspective to guide future research and system optimization in the context of plastic contamination. These insights are grounded in microbial stress-response frameworks and ecological resilience theory, providing a conceptual lens to interpret sludge system vulnerability under plastic-induced perturbations.